Critical Thinking in EFL Students' Argumentative Writing: Manifestations and Challenges - Arifin, Syaadiah; Ilyas, Hamzah Puadi (Universitas Hamzanwadi, 2025)
Critical thinking (CT) is widely recognized as an essential component of academic writing, yet EFL students often struggle to apply it effectively in argumentative essays. While previous studies have examined correlations between CT and writing quality or evaluated teaching interventions, less is known about how CT actually manifests in students’ written work and the challenges they encounter in real writing contexts. This study addresses this gap by exploring both the textual indicators of CT and students’ lived experiences of integrating it into their essays. The study involved 27 fifth-semester English education majors at a private university in Jakarta, Indonesia, with English proficiency ranging from intermediate to pre-advanced. Data were collected through two argumentative writing tasks, a focus group discussion, and document analysis. Thematic analysis and structured coding were used to identify CT indicators and challenges, with findings triangulated across data sources. Results showed that students demonstrated CT through coherent argumentation, use of evidence, engagement with counter-arguments, and organized essay structure. However, they struggled with organizing complex ideas, synthesizing information from multiple sources, and balancing creativity with logical reasoning, leading to disjointed arguments and superficial use of evidence. The study highlights the gap between theoretical CT standards and their practical application in EFL writing, underscoring the need for targeted instruction in argument structuring, source evaluation, and counter-argumentation.